Hukum Islam Nusantara: Diaspora Undang-Undang Malaka di Kesultanan Aceh Abad Ke-17 - Hasan Basori (Tashwirul Afkar, 2020)
Abstrak Tulisan ini membahas tentang diaspora Undang-Undang Malaka di Kesultanan Aceh abad ke-17 sebagai salah satu landasan berpikir hukum Islam Nusantara. Islam Nusantara yang sejak kelahirannya mengundang kontroversi, terutama dalam pola istinbath al-hukmi yang mengedapankan al-masha>lih sebagai basis kerangka pikirnya, akan didalami jejak historisnya dari abad ke-17, di mana hukum Islam selalu akomodatif terhadap hukum adat dan hukum sosial yang telah berlaku pada suatu masyarakat. Penelitian ini menggunakan pendekatan historis dengan menjadikan Undang-Undang Malaka abad ke-17 sebagai objek utamanya. Studi ini menemukan historitas hukum Islam yang datang ke Nusantara, dan menyisipkan dirinya dalam beberapa aspek hukum dan Undang-Undang setempat, dapat dipandang sebagai satu keberhasilan diaspora hukum Islam itu sendiri. Beberapa indikator keberhasilan diaspora hukum Islam dalam masyarakat Aceh abad ke-17 terletak pada hukum dagang dan ekonomi secara umum, dalam hukum pernikahan dan etika politik yang bernuansa islami. Treatment politik Islam, geliat ekonomi Islam, bahkan pola tata nilai yang dibawa Islam ke daerah Aceh pada masanya menjadi salah satu penyokong keberhasilan diaspora hukum Islam itu sendiri.   Abstract This paper discusses the Malacca diasporic law in the 17th century of the Aceh Sultanate as one of the foundations for thinking about Islamic law in the archipelago. Nusantara Islam, which since its birth has invited some controversies, especially in the pattern of istinbath al-hukmi which puts al-mashalih as the basis of its framework, needs to be explored about its historical traces from the 17th century where Islamic law has always accomodative to customary and social law prevailed in the society. This research will employ a historical approach by making the 17th century Malacca Law as its main object. This paper found a historicity of Islamic law that came to the archipelago, and inserts itself in several lines of local laws and regulations, therefore it can be seen as a success of the Islamic legal diaspora itself. Some indicators of the success of the Islamic law diaspora in 17th century Acehnese society lie in commercial and economic law in general, in marriage law and political ethics that have Islamic nuances. This research views that the treatment of Islamic politics, the stretching of the Islamic economy, and even the pattern of values ​​that Islam brought to the Aceh region during its time became one of the supporters of the success of the Islamic Law diaspora itself. From that point of view, this study aims to find a structured formula for how Islamic law was able to influence the Aceh sultanate at that time. The formulations of the model and strategy of the Islamic law diaspora in the Aceh Sultanate at that time are the main findings to be achieved in this study.